The Impact of Learning Strategies on English as a Foreign Language Learners’ Reading Comprehension Skills Development - Wendaferew, Desta; Berlie, Abebe Damtew (Educational Challenges, 2024)
Purpose. The aim of this study was to examine the impact of explicit reading strategy teaching English as a foreign language (EFL) on Ethiopian grade eleven learners’ reading comprehension skills, particularly, reading for the gist, detail, vocabulary, inference, and reference skills. Methodology. A quasi-experimental design was used, involving eighty-seven students (43 students in the control and 44 students in the experimental group). The students of the experimental class were exposed to four months of explicit reading strategy training, but no training was given to the students in the control group. Reading comprehension tests were given to both groups before and after training. Results. The independent sample t–test revealed that there was no significant difference between the control and the experimental group in overall reading comprehension before the training, whereas the results of multivariate analysis of variance (MANOVA) for the post-test indicated students in the experimental group significantly outperformed their counterparts in terms of overall reading comprehension as well as the three reading comprehension skills, namely, reading for the gist, detail, and vocabulary. The post means of inference and reference skills for the experimental group were also higher than the post means of the control group though the differences were not statistically significant. Conclusions. The study concluded that explicit reading strategy training promotes Ethiopian students' reading comprehension skills; hence, EFL students should be adequately supported and encouraged to use reading strategies to circumvent their reading comprehension difficulties.